2002
DOI: 10.1093/ajcn/76.1.205
|View full text |Cite
|
Sign up to set email alerts
|

Variation in newborn size according to pregnancy weight change by trimester,,

Abstract: The use of measured prepregnancy weight in tests of the effect on newborn size of weight gain by time in pregnancy produces different results than does the use of recalled prepregnancy weight. Maternal weight change in the first trimester of pregnancy more strongly influences newborn size than does weight change in the second or third trimester.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
84
2
6

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(99 citation statements)
references
References 12 publications
7
84
2
6
Order By: Relevance
“…Weaknesses of the study include the moderate size and the focus on pregnancy weight gain during the first two trimesters. However, several reports have indicated that maternal weight gain in the first and second trimester may be stronger determinants of newborn size than weight gain in the third trimester of pregnancy (Abrams & Selvin, 1995;Brown et al, 2002;Guihard-Costa et al, 2002). In any case, even if weight gain during the third trimester has its own determinants and consequences, this does not affect the findings of the present study.…”
Section: Discussioncontrasting
confidence: 47%
“…Weaknesses of the study include the moderate size and the focus on pregnancy weight gain during the first two trimesters. However, several reports have indicated that maternal weight gain in the first and second trimester may be stronger determinants of newborn size than weight gain in the third trimester of pregnancy (Abrams & Selvin, 1995;Brown et al, 2002;Guihard-Costa et al, 2002). In any case, even if weight gain during the third trimester has its own determinants and consequences, this does not affect the findings of the present study.…”
Section: Discussioncontrasting
confidence: 47%
“…weight gain during the first trimester in pregnant women strongly predicts subsequent fetal growth [25]. By 90 dG, NR maternal baboons had lost 9.1% total body weight.…”
Section: Maternal and Fetal Growth-maternalmentioning
confidence: 99%
“…Birthweight by gestational age can be influenced by race, 3-8 ethnicity within and between races, 4,9-14 socioeconomic status, 15 gestational diabetes, 16 maternal smoking, maternal height and weight, 17 maternal weight gain during pregnancy, 18 and the newborn's sex. [3][4][5] Second-generation immigrants have been shown to have larger birthweight newborns than their first-generation counterparts.…”
Section: Introductionmentioning
confidence: 99%